Solving Some Linear and Nonlinear PDEs Using Laplace Adomian Decomposition Method - Attaullah (Journal of Nepal Mathematical Society, 2018)
In this paper, Laplace Adomian decomposition method (LADM) is applied to solve linear and nonlinear partial differential equations (PDEs). With the help of proposed method, we handle the approximated analytical solutions to some interesting classes of PDEs including nonlinear evolution equations, Cauchy reaction-diffusion equations and the Klien-Gordon equations.